PENGARUH PENGGUNAAN LEMBAR KERJA SISWA TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS III SD N KOTAGEDE 3 YOGYAKARTA TAHUN PELAJARAN 2014/2015 - Eko Riswanto; B. Kusmanto (Universitas Sarjanawiyata Tamansiswa, 2015)
Abstract: The purpose of this study was to identify trends in mathematics achievement of students of class III SD N Koagede 3 Yogyakarta academic year 2014/2015. The population in this study were all students of class III SD N Kotagede 3 Yogyakarta consisting of four classes with a random sampling technique. Test the validity of the instrument items, level of difficulty, different power and reliability. Prerequisite test used test for normality of distribution and homogeneity of variance test data analysis using correlated t test. Comparatively no positive effect on the use of student worksheets grade mathematics achievement SD N Kotagede 3 Yogyakarta academic year 2014/2015 t -4,457 < -t -1,713 table. Thus the method can improve the students' worksheets grade math achievement SD Kotagede 3 Yogyakarta academic year 2014/2015.